DESIGN PROCESS ANALYSIS OF A MULTI-STOREY PARKING FACILITY AS FUNCTIONAL SUPPORT BUILDING - Endah Tisnawati; Dilla Eka Septiyanti; Mas Nadila Surya Nandini (MODUL, 2026)
Multi-story parking buildings play a critical role in addressing the challenges of expanding campus vehicle populations and limited land resources. However, design evaluations often focus on the building's final physical performance, while ignoring how technical decisions are made throughout the design process. This study aims to reconstruct and analyze the architectural design process of multi-story parking buildings as functional support structures to understand the influence of analysis stages, technical standard application, and decision-making on the final design quality. The research uses a qualitative approach, with comparative case studies, based on document analysis of two design alternatives for the same project, location, and program. The data includes site information, capacity calculations, application of national parking standards, design development records, and final drawings, which are then analyzed descriptively to trace the causal relationship between the depth of the process and the design results. The results show that both alternatives meet the minimum requirements, but the iterative, evidence-based process yields more efficient circulation, more rational structural integration, and higher operational readiness. The findings confirm that design quality is primarily determined by the depth and thoroughness of the design process, rather than by the building's formal expression alone.